Implementation and Evaluation of an Industry 4.0-Based Energy Monitoring System: A Case Study of PT Communication Cable Systems Indonesia Tbk - Kurnianto, Hardi; Puspitasari, Windi (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
The industrial shift to the 4.0 age necessitates the adoption of an energy monitoring system capable of giving real-time, precise data that is integrated into the manufacturing process. This research looks at the design and implementation of an Internet of Things (IoT)-based Energy Monitoring System (EMS) for PT Communication Cable Systems Indonesia Tbk (CCSI), a fiber optic cable manufacturing firm with a relatively high operating energy consumption. The system was created through the following stages: issue identification, architectural design, prototyping, field implementation, technical validation, and financial analysis. A total of 88 monitoring points were mapped using a mix of digital kWh meters, NodeMCU 8266, RS485-TTL, and Hi-Link power supply modules that were linked via Wi-Fi to a central server for real-time dashboard viewing. The installation results showed enhanced energy data visibility, accuracy of electrical parameter readings, less mistakes due to manual recording, and the ability to spot consumption anomalies using heatmap visualization and performance indicators. Return on Investment (ROI) research revealed net profits beginning in the 21st month with an initial ROI of 2% and increasing to a cumulative ROI of 73% by the 36th month. This study demonstrates that IoT-based EMS may improve energy efficiency, lower operating costs, and enhance digital transformation capabilities in the industrial industry